Data supporting - Thermal response of multi-layer UV crosslinked PEGDA hydrogels - Hakim Khalili, Mohammad; Afsar, Ashfaq; Zhang, Rujing; Wilson, Sandra; Goel, Saurav; Impey, Susan A.; Aria, Adrianus Indrat (Cranfield University, 2023)
All data sets are raw data from thermoresponse behaviour of hydrogels. 1. Swelling test for multi-150 um hydrogels with 1.8 mg/ml of photoabsorber.2. Swelling test for mono-5 mm hydrogels with 0 mg/ml of photoabsorber.3. Swelling test for multi-20 um hydrogels with 9 mg/ml of photoabsorber.4. Swelling test for mono-3 mm and mono-1.5 mm hydrogels with 0 mg/ml of photoabsorber.5. Cyclic test for multi-150 um hydrogels.6. Dried weight and solid residue weight of all hydrogels samples7. EWC, NWF, NVF-summary for all hydrogel samples8. DSC-TG-Thermogram-All sample types
Keywords: poly (ethylene glycol) diacrylate; projection lithography system; thermoresponsive hydrogel scaffold; Biomaterials